2018
DOI: 10.1186/s12913-018-3366-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for children with acute malnutrition at health center level in Uganda: a cross sectional study in West Nile region during the refugee crisis

Abstract: BackgroundArua district, in Uganda, hosts some of the largest refugee camps in the country. The estimated prevalence of moderate and severe acute malnutrition in children is higher than the national estimates (10.4 and 5.6% respectively, compared to 3.6 and 1.3%). This study aimed at assessing the quality of care provided to children with acute malnutrition at out-patient level in such a setting.MethodsSix facilities with the highest number of children with malnutrition were selected. The main tool used was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 20 publications
4
32
1
Order By: Relevance
“…High rates of abandons similar to what observed in this study were reported by other evaluations in sub-Saharan Africa 18. Abandons may be due to multiple underlying causes, including: low perception of the need/advantages for accessing care, difficulty in accessing care due to lack/cost of transports, conflicting priorities for the mother such as the need for working and attending other children, poor information about service provision, perception of poor QoC and lack of effective systems for tracing defaulters.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…High rates of abandons similar to what observed in this study were reported by other evaluations in sub-Saharan Africa 18. Abandons may be due to multiple underlying causes, including: low perception of the need/advantages for accessing care, difficulty in accessing care due to lack/cost of transports, conflicting priorities for the mother such as the need for working and attending other children, poor information about service provision, perception of poor QoC and lack of effective systems for tracing defaulters.…”
Section: Discussionsupporting
confidence: 92%
“…The significant heterogeneity in health outcomes detected among HCs, in particular for children with MAM, is in line with previous observations, reporting large heterogeneity in QoC, even among nearby facilities 17 18 35. Literature and experience in the field have showed that the identification of ‘best performers’, and their appointment as local drivers of a quality improvement process (ie, by actively engaging champions in diffusing best practices in the nearby facilities), can actually help implementing changes 34.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, due to a lack of simple validated methods, malnutrition screening is not widely and correctly performed [17,18]. Research studies conducted in South Africa and Uganda have shown that health professionals have inadequate knowledge of available nutritional status interpretation tools as gaps have been identified [19,20]. Moreover, the level of evidence on nutritional screening tools to predict early malnutrition at community levels in high disease burdened settings such as SSA is unclear.…”
Section: Introductionmentioning
confidence: 99%